Resistance Characteristics of Watermelon Cultivars to Fusarium oxysporum f. sp. niveum - Soo Min Lee; Eun Ju Jo; Hun Kim; Gyung Ja Choi (Research in Plant Disease, 2023)
Fusarium wilt, caused by Fusarium oxysporum f. sp. niveum (Fon) is a serious disease in watermelon cultivation. Most of commercialized watermelon cultivars to Fusarium wilt are susceptible in Korea. Fon isolates were divided into four races (races 0, 1, 2, and 3), based on pathogenicity in four watermelon differentials including ‘Sugar baby’, ‘Charleston gray’, ‘Calhoun gray’ and ‘PI-296341-FR’. We obtained 7 isolates of Fon and tested to determine race of the fungal strains. Fon KACC 40902 and Fon HA were race 0 and Fon NW1, Fon NW2, Fon CW and Fon KACC 40901 were race 1. And Fon KACC 40905 was race 2, but race 3 isolate of Fon was not founded. We also tested virulence of seven Fon isolates on three-susceptible cultivars of watermelon. The isolates showed different virulence on the cultivars. In addition, to study the resistance characteristics of watermelon to Fon, we selected three moderately or highly resistant cultivars of watermelon and occurrence of Fusarium wilt in seedlings of the cultivars by seven Fon isolates was investigated. Among them, ‘Calhoun gray’ is highly resistant to six Fon isolates except Fon KACC 40905. On the other two cultivars, disease severity of Fusarium wilt caused by each isolate was positively correlated with the virulence of the Fon isolates. The results suggest that resistance of the watermelon cultivars to Fon isolates is likely affected by the virulence of the pathogen.